Barcelona. "Entrada á el puerto del vapor Ruso 'Zirianin'". Welcomed by CNT/FAI. Combina (left). Copied from CNT collection
Barcelona. "Entrada á el puerto del vapor Ruso 'Zirianin'". Welcomed by CNT/FAI. Combina (left). Copied from CNT collection.